An ion-conducting halide composite electrolyte membrane, a method for preparing the same, and use thereof
Patent Information
- Application Number
- CN202611117116.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-27
- Publication Date
- 2026-11-03
AI Technical Summary
Existing halide solid electrolyte powder tablets rely on high pressure, resulting in brittle tablets that are difficult to prepare thin, self-supporting films. They also have insufficient adhesion to the electrode or lithium metal anode interface. When halide electrolytes come into direct contact with lithium metal anodes, interfacial side reactions are prone to occur, affecting long-term stability.
A high-halogen-content composite solid electrolyte membrane supported by an ion-conducting cellulose skeleton is constructed by introducing lithium salts such as LiFSI, LiTFSI, and LiDFOB and/or a small amount of pyrrolidineonium ionic liquids into the ethyl cellulose skeleton, combined with an anhydrous acetonitrile dispersion system and filter membrane-assisted deposition. This results in a peelable, bendable, and thickness-controllable composite electrolyte membrane, reducing reliance on traditional high-pressure tableting and avoiding hydration and dehydration control issues caused by water immersion.
It achieves thin-layering and good self-supporting capabilities, while taking into account high inorganic content, flexibility and ion conduction. It improves the continuity of ion conduction between particles and the interface buffering capacity, reduces lithium metal interface side reactions and impedance growth, and is suitable for thin-layering and low-pressure assembly of all-solid-state batteries.
Smart Images

Figure CN123034019A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of lithium-ion battery technology, specifically relating to an ion-conducting halide composite electrolyte membrane, its preparation method, and its application. Background Technology
[0002] All-solid-state batteries, which use solid electrolytes instead of traditional liquid electrolytes, are considered a key direction for improving the energy density and safety of lithium batteries. Existing solid electrolytes mainly include oxide, sulfide, polymer, and halide systems. Among them, halide solid electrolytes such as Li3InCl6 and Li3YCl6 have attracted considerable attention in recent years due to their high room-temperature ionic conductivity, good compatibility with high-voltage cathodes, and relatively mild synthesis conditions.
[0003] However, halide solid electrolytes typically exist in powder form, and current laboratory tests mostly employ powder compression, where electrolyte powder is pressed into sheet-like electrolytes under high pressure and then stacked with positive and negative electrodes. This method has significant limitations: First, the compression process relies on high pressure, the preparation steps are cumbersome, and problems such as large electrolyte layer thickness, high sheet brittleness, insufficient flexibility, and poor interface adhesion arise, which are not conducive to thin-layer fabrication and are difficult to adapt to large-area thin-layer manufacturing; Second, the compressed sheet is relatively brittle and easily cracks when bent or peeled; Third, the contact between the powder compression and the electrode interface depends on external pressure, resulting in insufficient uniformity of interface adhesion; Fourth, halide solid electrolytes are sensitive to humidity, and exposure to high humidity environments can easily lead to hydration, water absorption, or structural changes, thereby affecting ion transport and battery stability.
[0004] Existing technologies mainly fall into two categories. One category involves preparing self-supporting halide solid electrolyte films using inorganic nanofiber frameworks. For example, patent application CN116706215A discloses a method for preparing self-supporting halide solid electrolyte films. This method uses nanofiber membranes such as ZrO2, SiO2, Al2O3, TiO2, and glass fibers as the supporting framework. A halide precursor solution is impregnated into the nanofiber membrane, followed by heat treatment and pressing to obtain a self-supporting halide solid electrolyte film with a thickness of approximately 10–100 μm.
[0005] Another method involves preparing Li3InCl6 solid electrolyte membranes by impregnating nonwoven fabrics. For example, patent application CN118367203A discloses a Li3InCl6 solid electrolyte membrane and its preparation method. Li3InCl6 is mixed with water to form a halide-water mixture, and then nonwoven fabric is impregnated in it, allowing Li3InCl6 to enter the internal pores and surface of the nonwoven fabric. Subsequently, the membrane is dried at a temperature not exceeding 105°C and then baked at 100~130°C to solidify Li3InCl6 in the nonwoven fabric, forming a solid electrolyte membrane.
[0006] However, the inorganic nanofiber skeleton route relies on rigid support, impregnation, heat treatment and pressing steps, and lacks flexible bonding and interfacial buffering. The nonwoven water impregnation route uses water as a medium, which has problems with hydration, dehydration control and residual moisture treatment, which may affect the structural stability and interfacial stability of halide electrolytes.
[0007] While conventional binders can improve the film-forming properties of inorganic powders, most primarily function as mechanical binders with limited lithium-ion conductivity. This can lead to the formation of non-conductive barrier phases between halide particles, resulting in discontinuous ion transport pathways. Ethyl cellulose possesses some flexibility and film-forming ability, but its functionality is insufficient if used solely as a general binder. Therefore, it is necessary to transform ethyl cellulose from a simple supporting framework into an ion-conducting framework containing lithium salts or ionic liquids. This would allow it to both connect halide particles and participate in constructing lithium-ion migration channels between particles, while also mitigating side reactions to some extent. Summary of the Invention
[0008] Current technologies suffer from several technical problems, including the dependence of halide solid electrolyte powder tableting on high pressure, brittle tablets, difficulty in preparing thin self-supporting films, insufficient adhesion to the electrode or lithium metal anode interface, and the tendency for halide electrolytes to undergo interfacial side reactions and form high-resistivity interfacial layers when in direct contact with the lithium metal anode, thus affecting long-term stability.
[0009] Therefore, the purpose of this invention is to overcome the above-mentioned defects of the prior art and provide an ion-conducting cellulose skeleton-supported high halide-content composite solid electrolyte film and its filter membrane-assisted preparation method. By introducing lithium salts such as LiFSI, LiTFSI, and LiDFOB and / or a small amount of pyrrolidineonium-based ionic liquids into the ethyl cellulose skeleton phase, the ethyl cellulose phase is transformed from a purely mechanically binding phase into a bridging phase with lithium-ion conductivity. At the same time, a peelable, bendable, and thickness-controllable high halide-content composite electrolyte film is constructed through an anhydrous acetonitrile dispersion system and filter membrane-assisted deposition, reducing the reliance on traditional high-pressure pressing, avoiding the hydration and dehydration control problems caused by aqueous immersion, and improving the film's flexibility, film-forming properties, interparticle ion conduction continuity, interface buffering capacity, and all-solid-state battery assembly adaptability.
[0010] The present invention first provides an ion-conducting halide composite electrolyte membrane, wherein, by total mass ratio, the ion-conducting halide composite electrolyte membrane comprises 90%~96% halide solid electrolyte, 3%~7% ethyl cellulose, and 1%~3% ion-conducting components; the ion-conducting components include lithium salts.
[0011] The halide solid electrolyte of this invention is Li3InCl6.
[0012] The lithium salt described in this invention is at least one of LiFSI (lithium bisfluorosulfonylimide, CAS No. 171611-11-3), LiTFSI (lithium bistrifluoromethanesulfonylimide, CAS No. 90076-65-6), or LiDFOB (lithium difluorooxalateborate, CAS No. 409071-16-5), preferably LiFSI or LiTFSI.
[0013] Preferably, the ion-conducting component comprises 0%~1% ionic liquid and 1%~3% lithium salt by total mass ratio; when the ionic liquid is 1%, the lithium salt is 2% by total mass ratio; when the ionic liquid is 0%, the lithium salt is 1%~3%.
[0014] The ionic liquid is a pyrrolidine-onium or piperidinium-onium ionic liquid, preferably one of PYR13FSI (N-methyl-N-propylpyrrolidine-onium bis(trifluoromethanesulfonyl)imide salt, CAS No. 852620-97-4), PYR13TFSI (N-methyl-N-propylpyrrolidine bis(trifluoromethanesulfonyl)imide salt, CAS No. 223437-05-6) or PP13TFSI (N-propyl-N-methylpiperidine bis(trifluoromethanesulfonyl)imide salt, CAS No. 608140-12-1), more preferably PYR13FSI.
[0015] In some preferred embodiments, the ion-conducting halide composite electrolyte membrane comprises, by total mass, 94% Li3InCl6, 4.5% ethyl cellulose, and 1.5% LiFSI.
[0016] The preferred ratio of Li3InCl6:ethylcellulose:LiFSI is 94:4.5:1.5 by total mass because this ratio achieves a good balance between high halide content, self-supporting film-forming properties, room temperature ionic conductivity, and cycling stability.
[0017] When the content of ethyl cellulose and lithium salt is too low, for example, when the content of Li3InCl6 is increased to about 96 wt%, although the inorganic content of the membrane is high, the flexibility and interfacial buffering capacity are insufficient, and the cycle retention rate decreases. When the content of ethyl cellulose and lithium salt is too high, for example, when the content of ethyl cellulose is 7 wt% and LiTFSI is 3 wt%, the increase in the proportion of organic phase will reduce the proportion of inorganic continuous conduction between particles, resulting in a decrease in room temperature ionic conductivity.
[0018] Therefore, the preferred ratio is to maintain the conductivity at the mS / cm level while taking into account peelability, self-support, bending integrity and battery cycle stability.
[0019] In the ion-conducting halide composite electrolyte membrane of this invention, a halide solid electrolyte such as Li3InCl6 serves as the main ion-conducting phase, providing a fast lithium-ion migration channel. Ethyl cellulose provides a flexible framework and particle bridging function, with lithium salts or ionic liquids distributed within this organic framework, transforming the framework phase from merely a binder into an interparticle bridging phase with lithium-ion conductivity.
[0020] In terms of microstructure, Li3InCl6 particles can be stacked in rod-like, granular, or clustered forms, with the ethyl cellulose-lithium salt composite phase distributed between the particles, forming a continuous or semi-continuous bridging structure. This structure retains the ion conductivity provided by the high halide content while reducing the obstruction to interparticle transport by ordinary non-conductive binders, and simultaneously endows the film with a certain degree of flexibility, interfacial buffering capacity, and operability.
[0021] The composite solid electrolyte film has a thickness of 5-200 μm, preferably 20-100 μm, more preferably about 20-40 μm, and even more preferably 26-28 μm. The film can be peeled off from the supporting filter membrane and remains intact after bending. Because the lithium salt or ionic liquid is distributed in the ethyl cellulose framework, the interparticle interface changes from simple mechanical bonding to a bridging interface that combines flexible support and lithium-ion conduction capability.
[0022] The present invention also provides a method for preparing the ion-conducting halide composite electrolyte membrane, comprising the following steps: Step 1: Disperse the halide solid electrolyte, ethyl cellulose and ion-conducting components in an organic solvent and stir to form a homogeneous slurry; the organic solvent is preferably anhydrous acetonitrile; Step 2: Pour the slurry from Step 1 into a filtration device equipped with a polymer filter membrane, filter and dry to remove organic solvent, and obtain the ion-conducting halide composite electrolyte membrane.
[0023] In step 2, the use of a filter membrane-assisted deposition can restrict slurry flow and particle migration during solvent removal. It mainly serves as a temporary support and liquid-solid separation medium in the filter membrane-assisted deposition process, allowing Li3InCl6 particles to be uniformly stacked in the film, reducing the risk of local agglomeration and cracking. It is not a necessary component of the final composite electrolyte membrane.
[0024] Preferably, the filtration device described in step 2 is a vacuum filtration device. During production, continuous membrane fabrication can be achieved by methods such as continuous vacuum belt filtration, roller-to-roll vacuum assisted deposition, slot coating combined with vacuum desolventizing, and blade coating combined with porous support layer suction.
[0025] The present invention also provides an all-solid-state lithium-ion battery using the ion-conducting halide composite electrolyte membrane described in the present invention.
[0026] This invention constructs an ion-conducting cellulose composite framework by introducing a small amount of lithium salt into the ethyl cellulose framework phase, and, if necessary, further introducing a small amount of ionic liquid as a plasticizer and interface wetting component. Then, a filter membrane-assisted wet deposition is used to form a composite solid electrolyte film with high halide content, which can still be peeled, bent, and has controllable thickness.
[0027] Meanwhile, while maintaining high room temperature ionic conductivity, the film can improve the continuity of ion conduction between particles, mechanical integrity, and interfacial contact capability. It also buffers the lithium metal / halide electrolyte interface contact through a cellulose-lithium salt composite framework, slowing down lithium metal side interface side reactions and impedance growth, thereby improving its adaptability and cycle stability in lithium metal all-solid-state batteries.
[0028] Specifically, the beneficial effects of the present invention are as follows: 1. Excellent thin-film properties and self-supporting ability. Compared with traditional halide powder tableting, this invention obtains a peelable film through wet deposition assisted by a filter membrane, and the film thickness can be controlled at the tens of micrometer level, which is beneficial to reducing the thickness of the electrolyte layer in the battery.
[0029] 2. Balancing high inorganic content, flexibility, and ion conductivity. Ethyl cellulose is used in relatively low amounts, avoiding significant dilution of the Li3InCl6 ion-conducting phase, while also serving as a framework to connect particles. Further introduction of LiFSI, LiTFSI, or LiDFOB allows the ethyl cellulose framework phase to form a bridging interface with lithium-ion conductivity, reducing the obstruction of interparticle ion migration by ordinary non-conductive binders.
[0030] 3. Maintaining high room temperature ionic conductivity. In the examples, the room temperature ionic conductivity of the composite film can reach the mS / cm level. Compared with the simple ethyl cellulose binder system, the addition of lithium salt or ionic liquid is beneficial to increasing the concentration of migratable lithium ions in the organic framework phase, thereby improving interparticle interfacial transport.
[0031] 4. Improved lithium metal interface stability. The ion-conducting cellulose framework can provide a flexible buffer and ion transport channel between lithium metal and halide particles, helping to reduce the risks of local contact inhomogeneity, interface polarization, and dendrite penetration.
[0032] 5. The process is mild and easy to scale up. The preparation process mainly includes dispersion, filtration, drying and exfoliation. It does not require high-temperature sintering, nor does it require high-pressure pressing during the film-forming stage. It can be expanded to include doctor blade coating, roller coating, continuous filtration deposition or roll-to-roll wet film formation.
[0033] 6. Compared with pure Li3InCl6 pellets or ordinary PVDF bonding systems, the composite film of the present invention can achieve a self-supporting, bending-complete, low-pressure impedance growth and reduced lithium metal interface side reactions while maintaining an ionic conductivity in the mS / cm range. Therefore, it is more suitable for thin-layering of all-solid-state batteries and low-pressure assembly. Attached Figure Description
[0034] Figure 1 Flowchart for the filter membrane-assisted preparation of Li3InCl6-ethylcellulose-lithium salt composite solid electrolyte membrane.
[0035] Figure 2 The SEM cross-section (scale bar 10 μm, electron high voltage (EHT) 20.00 kV, signal type (Signal A) primary and secondary electron (SE1), working distance (WD) 8.0 mm, magnification (Mag) 1.00 K×) and surface morphology (scale bar 30 μm, blue arrow indicates film thickness 26.24 μm) of the Li3InCl6-ethylcellulose-LiFSI composite solid electrolyte film are shown.
[0036] Figure 3 This is a diagram showing the self-supporting and bending states of the composite solid electrolyte membrane in Example 1. Figure 3 The left image shows a self-supporting disc after punching; Figure 3 The right image shows the bent state.
[0037] Figure 4 The graphs are the first cycle charge-discharge curves for Examples 2, 5, and Comparative Example 2.
[0038] Figure 5 The graphs show the 100-cycle performance of Examples 1 to 5 and Comparative Examples 1 to 2.
[0039] Figure 6 The graph shows a comparison of the relative impedance values of different samples under different pressures (S1 is the pure Li3InCl6 electrolyte membrane obtained in Comparative Example 1, S2 is the Li3InCl6-PVDF-LiFSI composite electrolyte membrane obtained in Comparative Example 2, S3 is the Li3InCl6-ethylcellulose composite electrolyte membrane obtained in Comparative Example 3, S4 is the Li3InCl6-ethylcellulose-LiFSI composite electrolyte membrane obtained in Example 1, and S5 is the Li3InCl6-ethylcellulose-LiFSI-ionic liquid composite electrolyte membrane obtained in Example 5).
[0040] Figure 7The comparison shows the interfacial impedance growth and constant current charge-discharge polarization of different samples after contact with lithium metal (S1 is the pure Li3InCl6 electrolyte membrane obtained in Comparative Example 1, S2 is the Li3InCl6-PVDF-LiFSI composite electrolyte membrane obtained in Comparative Example 2, S3 is the Li3InCl6-ethylcellulose composite electrolyte membrane obtained in Comparative Example 3, S4 is the Li3InCl6-ethylcellulose-LiFSI composite electrolyte membrane obtained in Example 1, and S5 is the Li3InCl6-ethylcellulose-LiFSI-ionic liquid composite electrolyte membrane obtained in Example 5). Figure 7 In this context, 'a' represents the increase in interfacial impedance during the Li / film / Li settling process. Figure 7 In this context, b represents the change in polarization voltage during the cycling process of a symmetrical battery. Detailed Implementation
[0041] 1. Preparation method of ion-conducting halide composite electrolyte membrane Preparation of ion-conducting halide composite electrolyte membranes, such as Figure 1 As shown.
[0042] (1) Preparation of Li3InCl6 powder Anhydrous lithium chloride and anhydrous indium chloride were mixed and dissolved at a Li:In molar ratio of 3:1. Most of the water was then removed under an absolute pressure not exceeding 10 kPa and a temperature of 80~100℃. The mixture was then dried at 200℃ for 6 h in a vacuum drying oven (model HHM-6090) to obtain Li3InCl6 powder. The obtained Li3InCl6 was used as the main material for the halide solid electrolyte.
[0043] (2) Preparation of dispersion slurry Li3InCl6 powder, ethyl cellulose and lithium salt were added to anhydrous acetonitrile and slowly stirred magnetically with a magnetic stirrer (model MHS4PRO) in an inert atmosphere or dry environment until the powder was uniformly dispersed in the solvent to obtain a halide-ethyl cellulose-lithium salt composite dispersion slurry.
[0044] (3) Filter membrane-assisted deposition The composite dispersion slurry obtained in step (2) was slowly poured onto the surface of a polymer filter membrane (manufacturer MF-Millipore, catalog number SMWP0190R). Most of the acetonitrile was removed using a vacuum filtration device, with a filtration time of approximately 1 hour. During this process, the solvent was removed along the thickness direction, and Li3InCl6 particles gradually deposited on the filter membrane surface. The ethyl cellulose-lithium salt composite phase formed a connecting framework and ion-conducting bridge phase between the particles, thus constructing a dense but still continuous conductive channel thin film precursor.
[0045] (4) Vacuum drying and peeling The film precursor obtained in step (3) was placed in a vacuum drying oven and dried at 80°C for 12 h to further remove residual acetonitrile. After drying, the resulting film was peeled off from the polymer filter membrane to obtain a translucent or milky white Li3InCl6-ethylcellulose-lithium salt composite solid electrolyte film. Before peeling, a dense Li3InCl6-ethylcellulose-lithium salt composite solid electrolyte film could be obtained by applying a light pressure of 50 MPa for 1 min.
[0046] 2. The preparation method of PYR13FSI is as follows: N-methylpyrrolidine and 1-bromopropane were mixed in a molar ratio of 1:1.05 to 1:1.20 and reacted in acetonitrile or anhydrous ethanol at 60–80 °C for 12–24 h to obtain N-methyl-N-propylpyrrolidine onium bromide. After the reaction was completed, the solvent was removed, and the mixture was washed with ethyl acetate or diethyl ether to remove unreacted small molecule starting materials. Subsequently, the obtained pyrrolidine onium bromide was dissolved in deionized water or an acetonitrile / water mixture (acetonitrile to water volume ratio of 1:1 to 4:1, preferably 2:1), and an equimolar or slightly excess lithium bisfluorosulfonyl imide (LiFSI) was added. The mixture was stirred at room temperature for 4–12 h to perform anion exchange, generating N-methyl-N-propylpyrrolidine onium bisfluorosulfonyl imide (PYR13FSI).
[0047] After organic phase extraction and water washing until no halogen ions remain, the product is vacuum dried at 80~100℃ for 24~48 h to obtain a colorless or light yellow PYR13FSI ionic liquid for later use.
[0048] In this invention, PYR13FSI can also be a commercial product, which can be used directly after being dehydrated by molecular sieves or dried in a vacuum drying oven. Its main function is to improve the flexibility and interfacial wettability of the ethyl cellulose-lithium salt composite skeleton.
[0049] Example 1 1. Preparation of Li3InCl6-ethylcellulose-lithium salt composite solid electrolyte film (1) A certain amount of Li3InCl6 powder was placed in a vacuum drying oven and dried at 80℃ for 12 h to remove trace amounts of moisture and residual solvent adsorbed on the powder surface. After drying, the Li3InCl6 powder was transferred to an anhydrous and oxygen-free argon glove box (manufacturer Mbraun), and the O2 / H2O content in the glove box was controlled to be less than 0.1 ppm. The powder was then lightly ground in an agate mortar for 10 min to disperse it evenly for later use.
[0050] (2) In an anhydrous and oxygen-free argon glove box, take 94 mg of ground Li3InCl6 powder, 4.5 mg of ethyl cellulose, and 1.5 mg of LiFSI, and add them to 1 mL of anhydrous acetonitrile. Place the above mixture in a sealed glass bottle and stir at 200 r / min at room temperature for 2 h to uniformly disperse the Li3InCl6 powder, ethyl cellulose, and LiFSI in the anhydrous acetonitrile, forming a milky white homogeneous slurry.
[0051] (3) The obtained slurry was slowly poured into a vacuum filtration device equipped with a polymer filter membrane for filter membrane-assisted deposition, and then filtered under vacuum for 1 h to remove most of the acetonitrile solvent. After filtration, the filter membrane with the composite electrolyte layer deposited was transferred to a vacuum drying oven and dried under vacuum at 80°C for 12 h. After drying, the Li3InCl6-ethylcellulose-LiFSI composite solid electrolyte film was peeled off from the surface of the filter membrane to obtain a bendable, self-supporting Li3InCl6-ethylcellulose-LiFSI composite electrolyte film with an ion-conducting organic framework (SEM cross-section and surface morphology images are shown in the figure). Figure 2 (As shown), for later use.
[0052] 2. Electrode preparation and mold battery assembly NCM111 positive electrode active material and Li3InCl6 solid electrolyte were thoroughly mixed at a mass ratio of 7:3 and ground evenly to obtain the composite positive electrode material. In an anhydrous and oxygen-free argon glove box, 20 mg of the composite positive electrode material was evenly spread on one side of the Li3InCl6-ethyl cellulose-LiFSI composite electrolyte film, and pressed for 1 min at 147 MPa using a manual tablet press (model TOPE-TY-YP-15) to ensure full contact between the positive electrode composite material and the electrolyte film. Then, a lithium metal sheet was attached to the other side of the composite electrolyte film and pressed for 1 min at 98 MPa to obtain a Li / composite electrolyte film / NCM111 all-solid-state battery.
[0053] Example 2 1. Preparation of Li3InCl6-ethylcellulose-lithium salt composite solid electrolyte film (1) A certain amount of Li3InCl6 powder was placed in a vacuum drying oven and dried under vacuum at 80℃ for 12 h. The dried powder was then transferred to an anhydrous and oxygen-free argon glove box, and the O2 / H2O content was controlled to be less than 0.1 ppm. The powder was then ground in an agate mortar for 10 min to fully disperse the powder particles and reduce agglomeration. The powder was then ready for use.
[0054] (2) In an anhydrous and oxygen-free argon glove box, 96 mg of ground Li3InCl6 powder, 3 mg of ethyl cellulose, and 1 mg of LiFSI were added to 1 mL of anhydrous acetonitrile. The mixture was placed in a sealed container and stirred at room temperature for 2 h at a stirring rate of 200 r / min using a magnetic stirrer to ensure that a small amount of ethyl cellulose and LiFSI were evenly distributed among the Li3InCl6 powder. In this example, the halide content was increased to 96 wt% to verify the feasibility of film formation of ion-conductive framework composite films under high halide content conditions.
[0055] (3) The obtained slurry was slowly poured into a vacuum filtration device equipped with a polymer filter membrane, allowing the slurry to be uniformly deposited on the filter membrane surface. Vacuum filtration was then performed for 1 h to remove most of the acetonitrile solvent and to allow the Li3InCl6 particles to form a continuous stacked layer with the assistance of the ethyl cellulose-LiFSI composite framework. After filtration, the sample was placed in a vacuum drying oven at 80℃ for 12 h. After drying, the composite membrane was peeled off from the filter membrane surface to obtain a self-supporting Li3InCl6-ethyl cellulose-LiFSI composite solid electrolyte membrane with high Li3InCl6 content, for later use.
[0056] 2. Electrode preparation and mold battery assembly: NCM111 positive electrode active material and Li3InCl6 solid electrolyte were thoroughly mixed at a mass ratio of 7:3 and ground evenly to obtain the composite positive electrode material. In an anhydrous and oxygen-free argon glove box, 20 mg of the composite positive electrode material was evenly spread on one side of the Li3InCl6-ethyl cellulose-LiFSI composite electrolyte film, and pressed at 147 MPa for 1 min using a manual press to ensure full contact between the positive electrode composite material and the electrolyte film. Then, a lithium metal sheet was attached to the other side of the composite electrolyte film and pressed at 98 MPa for 1 min to obtain a Li / composite electrolyte film / NCM111 all-solid-state battery.
[0057] Example 3 1. Preparation of Li3InCl6-ethylcellulose-lithium salt composite solid electrolyte film (1) Place Li3InCl6 powder in a vacuum drying oven and dry it at 80℃ for 12 h to reduce the adsorbed water and solvent residue on the powder surface. After drying, transfer the powder to an anhydrous and oxygen-free argon glove box, control the O2 / H2O content to be less than 0.1 ppm, and grind it with an agate mortar for 10 min to form a relatively uniform dispersion state for later use.
[0058] (2) In an anhydrous and oxygen-free argon glove box, 90 mg of ground Li3InCl6 powder, 7 mg of ethyl cellulose, and 3 mg of LiTFSI were added to 1 mL of anhydrous acetonitrile. After sealing the mixture, it was stirred at 200 r / min at room temperature for 2 h to allow the ethyl cellulose and LiTFSI to be fully dispersed in the solvent and to coat or connect the Li3InCl6 particles. In this example, the organic framework and lithium salt content are increased to enhance the flexibility, peel integrity, and interparticle ion conduction continuity of the composite film.
[0059] (3) The obtained slurry was poured into a vacuum filtration device equipped with a polymer filter membrane. Vacuum filtration was used to uniformly deposit the composite slurry on the surface of the filter membrane. The filtration time was controlled to be 1 h. Then, the wet membrane and the filter membrane were transferred to a vacuum drying oven and pre-dried at 70°C for 4 h, and then vacuum dried at 80°C for 8 h to reduce the risk of membrane shrinkage and cracking during the drying process. After drying, the composite electrolyte membrane was peeled off from the surface of the filter membrane to obtain a Li3InCl6-ethylcellulose-LiTFSI composite solid electrolyte membrane with good flexibility.
[0060] 2. Electrode preparation and mold battery assembly NCM111 positive electrode active material and Li3InCl6 solid electrolyte were thoroughly mixed at a mass ratio of 7:3 and ground evenly to obtain the composite positive electrode material. In an anhydrous and oxygen-free argon glove box, 20 mg of the composite positive electrode material was evenly spread on one side of the Li3InCl6-ethyl cellulose-LiTFSI composite electrolyte membrane. The membrane was pressed at 147 MPa for 1 min using a manual press to ensure full contact between the positive electrode composite material and the electrolyte membrane. Then, a lithium metal sheet was attached to the other side of the composite electrolyte membrane and pressed at 98 MPa for 1 min to obtain a Li / composite electrolyte membrane / NCM111 all-solid-state battery.
[0061] Example 4 1. Preparation of Li3InCl6-ethylcellulose-lithium salt composite solid electrolyte film (1) Take a certain amount of Li3InCl6 powder and place it in a vacuum drying oven. Dry it under vacuum at 80℃ for 12 h. Transfer the dried powder to an anhydrous and oxygen-free argon glove box, control the O2 / H2O content to be less than 0.1 ppm, and grind it with an agate mortar for 10 min to keep the powder in a uniformly dispersed state for later use.
[0062] (2) In an anhydrous and oxygen-free argon glove box, 94.5 mg of pretreated Li3InCl6 powder, 4.5 mg of ethyl cellulose, and 1.0 mg of LiDFOB were added to 0.6 mL of anhydrous acetonitrile. After sealing the mixture, it was stirred at room temperature at a stirring rate of 200 r / min for 2 h to obtain a composite slurry with a high solid content. Compared with Example 1, this example reduces the amount of anhydrous acetonitrile and uses LiDFOB as an ion-conducting and interface-modifying component to prepare relatively thick or dense composite solid electrolyte films.
[0063] (3) The obtained high-solids content slurry was slowly poured into a vacuum filtration device equipped with a polymer filter membrane and vacuum filtered for 1 h to form a relatively dense deposition layer of Li3InCl6 particles, ethyl cellulose, and LiDFOB on the filter membrane surface. After filtration, the wet membrane was pre-dried under vacuum at 60℃ for 4 h, and then vacuum dried at 80℃ for 12 h. After drying, the membrane was peeled off from the filter membrane and further lightly pressed at 50 MPa for 1 min to improve the contact between membrane particles and the overall density, thus obtaining a Li3InCl6-ethyl cellulose-LiDFOB composite solid electrolyte membrane with adjustable thickness.
[0064] 2. Electrode preparation and mold battery assembly NCM111 positive electrode active material and Li3InCl6 solid electrolyte were thoroughly mixed at a mass ratio of 7:3 and ground uniformly to obtain the composite positive electrode material. In an anhydrous and oxygen-free argon glove box, 20 mg of the composite positive electrode material was evenly spread on one side of the Li3InCl6-ethyl cellulose-LiDFOB composite electrolyte membrane, and pressed at 147 MPa for 1 min using a manual press to ensure full contact between the positive electrode composite material and the electrolyte membrane. Then, a lithium metal sheet was attached to the other side of the composite electrolyte membrane and pressed at 98 MPa for 1 min to obtain a Li / composite electrolyte membrane / NCM111 all-solid-state battery.
[0065] Example 5 1. Preparation of Li3InCl6-ethylcellulose-lithium salt / ionic liquid composite solid electrolyte thin film (1) Place Li3InCl6 powder in a vacuum drying oven and dry it at 80℃ for 12 h. After drying, transfer the powder to an anhydrous and oxygen-free argon glove box and control the O2 / H2O content to be less than 0.1 ppm. Grind it in an agate mortar for 10 min to fully disperse the powder particles for later use.
[0066] (2) In an anhydrous and oxygen-free argon glove box, 92 mg of pretreated Li3InCl6 powder, 5 mg of ethyl cellulose, 2 mg of LiFSI, and 1 mg of PYR13FSI were added to 1.5 mL of anhydrous acetonitrile. After sealing the mixture, it was stirred at 200 r / min at room temperature for 3 h to improve the fluidity and dispersion uniformity of the slurry. In this example, a small amount of ionic liquid was introduced to improve the ionic conductivity and interfacial wettability of the organic framework phase and to prepare a more uniform thin-layer composite electrolyte membrane.
[0067] (3) The obtained low-solids content slurry was poured into a vacuum filtration device equipped with a polymer filter membrane in two batches. After the first pour, vacuum filtration was performed for 30 min to ensure uniform deposition of the bottom layer. The remaining slurry was poured in for the second batch, and vacuum filtration was performed for another 60 min to obtain a more uniform deposition layer. The sample was then pre-dried in a vacuum drying oven at 60℃ for 4 h, and then vacuum dried at 80℃ for 12 h. After drying, the composite membrane was peeled off from the filter membrane surface to obtain a relatively smooth and uniform Li3InCl6-ethylcellulose-LiFSI-ionic liquid composite solid electrolyte membrane for later use.
[0068] 2. Electrode preparation and mold battery assembly NCM111 positive electrode active material and Li3InCl6 solid electrolyte were thoroughly mixed at a mass ratio of 7:3 and ground evenly to obtain the composite positive electrode material. In an anhydrous and oxygen-free argon glove box, 20 mg of the composite positive electrode material was evenly spread on one side of the Li3InCl6-ethylcellulose-LiFSI-ionic liquid composite solid electrolyte membrane. The membrane was pressed at 147 MPa for 1 min using a manual press to ensure full contact between the positive electrode composite material and the electrolyte membrane. Then, a lithium metal sheet was attached to the other side of the composite electrolyte membrane and pressed at 98 MPa for 1 min to obtain the Li / composite electrolyte membrane / NCM111 all-solid-state battery assembly.
[0069] Low-pressure interfacial bonding and lithium metal interface stability verification: 92 mg of Li3InCl6 powder, 5 mg of ethyl cellulose, 2 mg of LiFSI, and 1 mg of PYR13FSI were added to 1.5 mL of anhydrous acetonitrile and stirred for 3 h. The mixture was then deposited in two portions in a vacuum filtration apparatus. After pre-drying at 60 °C for 4 h and vacuum drying at 80 °C for 12 h, the film was peeled off. The resulting film had a thickness of approximately 26 ± 2 μm and remained intact under bending and curling conditions, indicating that a small amount of ionic liquid can further improve the flexibility of the framework and the interfacial wettability.
[0070] Comparative Example 1 The solid electrolyte used in this comparative example was Li3InCl6 powder that had not undergone ion-conducting cellulose backbone composite modification. Specifically, 100 mg of pretreated Li3InCl6 powder was added to 1 mL of anhydrous acetonitrile and stirred at 200 r / min at room temperature for 2 h to disperse it in acetonitrile; then, it was subjected to membrane-assisted deposition, vacuum filtration, and vacuum drying at 80 °C.
[0071] Because no ethyl cellulose, lithium salt, or ionic liquid framework material was added to the system, the deposited layer was difficult to peel off completely after drying, resulting in a brittle film that was difficult to form a stable, self-supporting composite electrolyte film. The remaining preparation steps were the same as in Example 1.
[0072] Comparative Example 2 In this comparative example, a conventional binder was used instead of the ion-conducting ethyl cellulose backbone. Specifically, 94 mg of pretreated Li3InCl6 powder, 4.5 mg of polyvinylidene fluoride (PVDF), and 1.5 mg of LiFSI were added to 1 mL of anhydrous acetonitrile and stirred at 200 r / min at room temperature for 2 h. Subsequently, filter membrane-assisted deposition, vacuum filtration, and vacuum drying at 80 °C were performed.
[0073] Due to insufficient compatibility and bridging between polyvinylidene fluoride (PVDF) and Li3InCl6 particles, even with the introduction of lithium salt, it is difficult to form a uniform ion-conducting particle bridging network. After drying, the film is prone to cracking, localized detachment, or uneven particle distribution, and its flexibility and self-support are weaker than those of the ethyl cellulose-lithium salt composite system. The remaining preparation steps are the same as in Example 1.
[0074] Comparative Example 3 In this comparative example, a Li3InCl6-ethylcellulose composite system was used, but no lithium salt or ionic liquid was added. Specifically, 95 mg of Li3InCl6 powder and 5 mg of ethylcellulose were dispersed in anhydrous acetonitrile, followed by membrane-assisted deposition, filtration, and drying. The resulting film could be peeled off to some extent, but its room temperature ionic conductivity was lower than that of the LiFSI-containing system. The conductivity retention decreased after bending, indicating that relying solely on the mechanical framework of ethylcellulose is insufficient to fully address the issue of interparticle ion conduction continuity. The remaining preparation steps were the same as in Example 1.
[0075] Example 1: Ionic conductivity test The ionic conductivity was measured using the AC impedance method. The electrolyte membranes prepared in Examples 1-5 and Comparative Examples 1-3 were cut into 10 mm diameter discs and sandwiched between two stainless steel blocking electrodes to form an SS / electrolyte membrane / SS symmetrical test cell (SS represents inert stainless steel). During testing, a constant pressure of approximately 294 MPa was applied to the cell to ensure sufficient contact between the electrolyte membrane and the stainless steel electrodes. In Comparative Example 1, due to the difficulty in forming a complete self-supporting membrane, the pure powder was pressed into a 10 mm diameter disc under 294 MPa pressure as a reference for pure intrinsic ionic conductivity; the other examples and comparative examples used the prepared composite membranes for testing.
[0076] The electrochemical workstation was set to an AC impedance testing frequency range of 1 MHz to 1 Hz, with an AC disturbance voltage of 5 to 20 mV. After the test, the impedance value R of the electrolyte membrane was obtained based on the high-frequency intercept of the impedance spectrum or equivalent circuit fitting, and the thickness L and effective contact area S of the composite solid electrolyte membrane were measured. The ionic conductivity was calculated using the following formula: σLi + = L / RS Where, σLi + R is the lithium-ion conductivity, L is the AC impedance value, L is the thickness of the composite solid electrolyte membrane, and S is the effective contact area between the electrode and the composite solid electrolyte membrane.
[0077] Table 1 The results are shown in Table 1. Comparative Example 1 exhibits the highest ionic conductivity, primarily because it is a pure Li3InCl6 powder / tablet system, free of organic framework phases, resulting in minimal intrinsic ionic conduction resistance. However, this result only indicates that pure inorganic halide electrolytes inherently possess high ionic conductivity and does not necessarily represent their optimal overall performance as thin-film electrolytes.
[0078] Comparative Example 1 suffers from problems such as difficulty in complete peeling, difficulty in forming a stable self-supporting film, fragility during bending, poor interfacial contact under low pressure, and significant increase in interfacial impedance after contact with lithium metal. Examples 1-5, although their ionic conductivity is slightly lower than that of pure Li3InCl6, still maintains the mS / cm level, and possesses the combined advantages of peelability, self-support, bendability, smaller impedance increase under low pressure, and better interfacial stability with lithium metal. Taking Example 1 as an example, the self-supporting and bending states of the composite solid electrolyte membrane are as follows: Figure 3 As shown.
[0079] Test Example 2: Cyclic Test of All-Solid-State Battery The cycle performance of the all-solid-state battery was tested using the Li / electrolyte membrane / NCM111 mold batteries prepared in Examples 1-5 and Comparative Examples 1-3, including the following steps: 1. Place the all-solid-state battery at the test temperature and let it stand for 2 hours to allow the electrode-electrolyte interface to reach a relatively stable state; 2. Charge the battery with a constant current at a rate of 0.2C. The charging cutoff condition is when the battery voltage reaches the upper limit voltage. After charging is completed, let it stand for 5~10 minutes. 3. Discharge the battery using a constant current at a rate of 0.2C. The discharge cutoff condition is when the battery voltage reaches the lower limit voltage. After the discharge is completed, let it stand for 5~10 minutes. 4. Repeat steps 2 and 3, and record the charge / discharge capacity and capacity retention rate for each cycle to evaluate the cycle stability of the composite solid electrolyte membrane in all-solid-state batteries.
[0080] All-solid-state batteries with a Li / composite electrolyte membrane / NCM111 mold battery structure can be used to verify the interfacial compatibility between the ion-conducting cellulose skeleton composite electrolyte membrane and the NCM111 cathode and lithium metal anode.
[0081] Table 2 The test results are shown in Table 2. Figure 4 and Figure 5 As shown, the initial capacity of Examples 1 to 5 was 1.55 to 1.71 mAh, and the capacity retention rate after 100 cycles was 66.2% to 78.4%, which was higher than that of Comparative Examples 1 to 3.
[0082] Although Comparative Example 1 is a pure Li3InCl6 system with high intrinsic ionic conductivity, it lacks a flexible framework and interfacial buffer phase, resulting in a capacity retention of only 38.5% after 100 cycles. Comparative Example 2 uses a common PVDF binder, and its initial capacity and capacity retention are further reduced, indicating that common non-ionic conductive binders hinder interparticle lithium-ion transport. Comparative Example 3 does not contain lithium salts or ionic liquids, and although its performance is improved compared to Comparative Example 2, it is still lower than the examples, indicating that the ethyl cellulose framework alone is insufficient to form effective ionic conduction bridges.
[0083] Examples 1 and 5 showed better performance, indicating that the ethyl cellulose-lithium salt or ionic liquid composite framework can improve film integrity and interface stability while maintaining high ionic conductivity, thereby improving the cycle performance of all-solid-state batteries.
[0084] Detection Example 3 Verification of interfacial bonding and lithium metal interface stability under different pressures: The Li3InCl6 / ethyl cellulose / LiFSI electrolyte membrane prepared in Example 1, the Li3InCl6 / ethyl cellulose / LiFSI / PYR13FSI electrolyte membrane prepared in Example 5, and the electrolyte membranes prepared in Comparative Examples 1 to 3 were assembled into SS / electrolyte membrane / SS and Li / electrolyte membrane / Li structures, respectively. EIS (electrochemical impedance spectroscopy) at pressures of 10 MPa, 30 MPa, 50 MPa, and 100 MPa was tested using the SS / electrolyte membrane / SS method. The interfacial impedance changes of the Li / electrolyte membrane / Li after standing for 0 h, 24 h, and 72 h were also measured, along with the 0.1 mA / cm² interfacial impedance. 2 Constant current lithium deposition / stripping test behavior.
[0085] Table 3 The results show that Examples 1 and 5 exhibit smaller impedance increases under low pressure (e.g., Figure 6 As shown), the impedance growth and polarization increase in Examples 1 and 5 were slower, indicating that the ion-conducting cellulose composite framework can mitigate lithium metal side reactions and improve interfacial stability (e.g., Figure 7 (As shown in Table 3). Meanwhile, the results page of Table 3 shows that the ethyl cellulose-lithium salt / ionic liquid composite frameworks of Examples 1 and 5 can reduce the increase in contact resistance under low pressure and slow down the rise in interfacial resistance after contact with metallic lithium.
[0086] Meanwhile, Comparative Example 3 improved film-forming properties compared to Comparative Examples 1 and 2, and could be peeled off to a certain extent, but local micro-cracks still easily appeared after bending; its electrical conductivity, low pressure impedance and lithium metal interface stability were still significantly weaker than those of Examples 1 and 5, indicating that using ethyl cellulose alone can only provide mechanical support and cannot fully construct a continuous lithium-ion conduction channel.
[0087] In Examples 1 and 5, R10 / R100 was significantly reduced under low pressure, and the interfacial impedance growth and long-term charge-discharge polarization after Li / electrolyte membrane / Li standing for 72 h were also lower, indicating that the ethyl cellulose-lithium salt or ionic liquid composite framework can simultaneously improve interparticle ion conduction continuity, low-pressure interfacial adhesion, and lithium metal interface stability.
Claims
1. An ion-conducting halide composite electrolyte membrane, characterized in that, The composition, by total mass percentage, includes 90%–96% halide solid electrolyte, 3%–7% ethyl cellulose, and 1%–3% ion-conducting components; the ion-conducting components include lithium salts.
2. The ion-conducting halide composite electrolyte membrane according to claim 1, characterized in that, The halide solid electrolyte is Li3InCl6.
3. The ion-conducting halide composite electrolyte membrane according to claim 1, characterized in that, The lithium salt is at least one of LiFSI, LiTFSI, or LiDFOB.
4. The ion-conducting halide composite electrolyte membrane according to claim 1, characterized in that, The ion-conducting component comprises 0% to 1% ionic liquid and 1% to 3% lithium salt by total mass ratio.
5. The ion-conducting halide composite electrolyte membrane according to claim 1, characterized in that, The ionic liquid is at least one of pyrrolidine-onium or piperidinium ionic liquids.
6. The ion-conducting halide composite electrolyte membrane according to claim 5, characterized in that, The pyrrolidine-onium ionic liquid is N-methyl-N-propylpyrrolidine-onium bisfluorosulfonylimide salt.
7. The ion-conducting halide composite electrolyte membrane according to claim 1, characterized in that, The composition, by total mass percentage, includes 94% Li3InCl6, 4.5% ethyl cellulose, and 1.5% LiFSI.
8. The method for preparing the ion-conducting halide composite electrolyte membrane according to any one of claims 1 to 7, characterized in that... Includes the following steps: Step 1: Disperse the halide solid electrolyte, ethyl cellulose and ion-conducting components in an organic solvent and stir to form a homogeneous slurry; Step 2: Pour the slurry from Step 1 into a filtration device equipped with a polymer filter membrane, filter and dry to remove organic solvent, and obtain the ion-conducting halide composite electrolyte membrane.
9. The preparation method according to claim 8, characterized in that, The organic solvent mentioned in step 1 is anhydrous acetonitrile.
10. A fully solid-state lithium-ion battery, characterized in that, Use the ion-conducting halide composite electrolyte membrane according to any one of claims 1 to 7.
Citation Information
Patent Citations
Preparation method and product of self-supporting halide solid electrolyte film
CN116706215A
Li3InCl6 solid-state electrolyte membrane, preparation method thereof and solid-state battery
CN118367203A
